Influence of crop rotation and flutolanil on the diversity of fungi on peanut shells - Baird, R.E.; Brenneman, T.B.; Bell, D.K.; Sumner, D.R.; Minton, N.A.; Mullinix, B.G.; Peery, A.B. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1995)
Soilborne pathogens of peanut (Arachis hypogaea) often survive or over winter on peanut shells left on or in the soil. The effects of different crop rotations on the peanut shell mycobiota were compared in three field trials in 1992 and repeated in 1993. In two of the trials, plots grown continuously to peanut were either treated with the fungicide flutolanil or left untreated. Rotation practices varied with location and the crops in rotation with peanut were cotton (Gossypium hirsutum), rye (Secale cereale), bahiagrass (Paspalum notatum), and corn (Zea mays). In total, 31 different gene of fungi were isolated from shells. Over two-thirds of the isolates were Deuteromycotina, followed in frequency by Basidiomycetes, Ascomycetes, and Phycomycetes. The rotation practices affected the incidence of several pathogenic fungi (e.g., Fusarium spp., and Lasiodiplodia theobromae) in the peanut shells, but the results were not consistent across trials or years. Bahiagrass or corn grown in rotation with peanut reduced the frequency of Rhizoctonia solani AG-4 in shells. Rhizoctonia solani AG-2-2 and Macrophomina phaseolina were isolated at a greater level in the bahiagrass-peanut rotation. Where peanut was rotated with cotton with or without a winter cover crop of rye, plots containing rye had lower isolation rates for total fungi in 1992 than those without rye, but there was no différence in 1993. Also, several species of Fusarium were isolated more frequently from shells from plots rotated with rye. Flutolanil significantly lowered isolation rates of several fungi, including R. solani AG-4, in one trial in 1992. Total fungi isolated (all fungal isolates combined) in the flutolanil-treated plots were greater in 1993, but not in 1992 at one site. Isolation rates for the different gene and species of fungi differed on the two media utilized (malt-extract agar and malt-salt agar). In particular, Alternaria alternata and species of Fusarium were isolated more frequently on malt-salt agar, whereas L theobromae, R. solani AG-4 and Trichoderma spp. were more common on malt-extract agar.